A new subspecies in a Heliconius butterfly adaptive radiation (Lepidoptera: Nymphalidae) (2017)
A fundamental goal in evolutionary biology is to understand how evolutionary patterns and processes shape natural diversity. This, however, requires a complete characterization of the phenotypic and genetic variation between and within species. Here, we used molecular, morphological and behavioural data to describe a new and stable subspecies of Heliconius timareta, named Heliconius timareta linaresi subsp. nov. This race differs phenotypically from other red-coloured H. timareta and instead exhibits a black and yellow wing pattern more similar to Heliconius cydno. However, mtDNA, microsatellite and amplified-fragment length polymorphism data indicate a closer relationship with H. timareta than H. cydno and Heliconius melpomene. Larval morphology and host plant preferences are similar to other H. timareta and H. cydno races. Thus, our combined data indicate that this taxon is a novel subspecies of H. timareta, clearly differentiated from H. cydno and H. melpomene. © 2017 The Linnean Society of London.